Stakeholders no setor público: um estudo de caso na organização vencedora do prêmio Ceará gestão pública - Cavalcante, Rejane Albuquerque (2014)
The study of public organization in a democratic state is closely linked to the supply of public services to citizens. The bureaucratic organization, based on instrumental rationality, no longer responds to the society's expectations. The New Public Management arises in this context and, from this scenario, preceded by other quality programs in public service, was created in 2005 the National Public Management and Bureaucratization Program, named as GesPública. This Program came with the aim to build public organizations guided for citizen-focused outcomes. Given the complexity of the public organization, with its pluralism of interests that influence or should influence their management, it is known that the stakeholder theory can help to understand and assist public managers in the decision making task, based on the peculiarity of managing public organizations, the way in which they deal with critical political, social and economic aspects, involving a variety of external and internal customers that do not behave like actors, but citizens eager for the delivery of quality goods and public services. This research aims at categorizing stakeholders of a public organization winning the award for excellence in public administration, based on GesPública, a management standard. This is an exploratory, inductive research, classified as a qualitative one, as the dominant approach, although using quantitative components for the categorization of data. The research strategy adopted was the case study, with data collection conducted through desk research, interviews and focus groups. Data analysis was performed as model operationalization of the theoretical framework of Mitchell, Agle and Wood proposed by Fontes Filho and Martins (1999), later applied by Almeida, Fontes Filho and Martins (2000). As a result, in relation to the categorization of stakeholders, definitive, expectant and latent stakeholders were found. Of expectant, only dependents were identified in the organization, in which stakeholders possess legitimacy and urgency above the criticality factor k. Dormant, were only identified the organization discretionary stakeholders, who possess the attribute legitimacy with scores greater than k. Regarding the prioritization of stakeholders, the main considered by managers to carry out their actions and preparing their strategies are the care staff and the support staff, followed by the Department of Health, by the Schools of education and training in care and management areas, by educational institutions partners, the Ministries of Health and Education, the volunteers and the Department of Finance. From the identification of definitive stakeholders, we can infer that the organization denotes be worried about people development, organization knowledge management, involvement of society and cost optimization.